2016
DOI: 10.1590/s1806-37562015000000337
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic pulmonary resection by video-assisted thoracoscopy: the Brazilian experience (VATS Brazil study)

Abstract: Objective: The objective of this study was to describe the results of anatomic pulmonary resections performed by video-assisted thoracoscopy in Brazil. Methods: Thoracic surgeons (members of the Brazilian Society of Thoracic Surgery) were invited, via e-mail, to participate in the study. Eighteen surgeons participated in the project by providing us with retrospective databases containing information related to anatomic pulmonary resections performed by video-assisted thoracoscopy. Demographic, surgical, and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…Another study using the SBCT database, which included pulmonary resections by video-assisted thoracoscopic surgery, reported a surgical morbidity rate of 19.1% and a mortality rate of 2.0%. (2) In our study, morbidity is comparable to that in patients who underwent video-assisted thoracoscopic surgery. However, there was a significant reduction in postoperative mortality (1.6-2.0% vs. 0.5%).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Another study using the SBCT database, which included pulmonary resections by video-assisted thoracoscopic surgery, reported a surgical morbidity rate of 19.1% and a mortality rate of 2.0%. (2) In our study, morbidity is comparable to that in patients who underwent video-assisted thoracoscopic surgery. However, there was a significant reduction in postoperative mortality (1.6-2.0% vs. 0.5%).…”
Section: Discussionsupporting
confidence: 66%
“…In the last two decades, minimally invasive surgery has been established as the gold standard for the treatment of lung cancer. (1,2) Several studies have been published and confirmed the role of video-assisted thoracoscopic surgery in complex resections such as lobectomies and pneumonectomies. (3,4) Recently, robotic surgery has emerged as an alternative to conventional video-assisted thoracoscopic surgery, because it has the advantage of increasing the amplitude and precision of intracavitary maneuvers and movements, as well as improving visualization through three-dimensional imaging.…”
Section: Introductionmentioning
confidence: 96%
“…Video-assisted thoracoscopic surgery (VATS) has become a standard therapeutic modality for spontaneous pneumothorax, diagnostic biopsies for multiple pulmonary and pleural diseases [4,5], management of complicated pleural effusions and, for major resections of pulmonary masses with a much lower rate of complications than open thoracotomy [6,7]. VATS bleeding complications has been reported as low as 0.6%, the majority of which are mild and " in layers" to 4.3% in major resections due to vascular injuries in 50% of the cases [8]. In the actual case, VATS was performed for a pleural effusion drainage and biopsy with a presumptive diagnosis of pleural tuberculosis, having no trans-operative complications.…”
Section: Discussionmentioning
confidence: 99%
“…There was a big-time lapse since those first initial experiences until the publication of a large series of anatomic lung resections in Brazil (13). In that paper, the authors reported the outcomes of 649 major lung resections performed by 18 thoracic surgeons from 14 institutions from different parts of the country.…”
Section: Mis In Latin Americamentioning
confidence: 99%